Electromagnetically Induced Transparency in the Five-level Scheme of Cold \(^85\)Rb Atomic Vapour - Hai, Bui Thi Hong; Doai, Le Van; Son, Doan Hoai; Khoa, Dinh Xuan; Bang, Nguyen Huy; Trong, Pham Van; Phuong, Le Thi Minh; Anh, Nguyen Tuan (Communications in Physics, 2013)
In the framework of the semiclassical theory, we develop an analytical approach on electromagnetically induced transparency (EIT) in the medium consists of five-level cascade scheme of cold 85Rb atoms. In the weak field limit of the probe light, an analytical representation of EIT spectra is derived for the first time. Signatures of EIT spectra, including transparency efficiency, have been investigated. We see a tremendous agreement between our theoretical results and experimental observations.